The Impact Of Governance On Economic Development In Malawi - Ngalande, Frank Chimwemwe (University of the Witwatersrand, Johannesburg, 2024)
The concept and discourse of good governance has been given a lot of emphasis in the international development space. It is mostly emphasised as a critical element in developing countries that deploy various development policies with little or no improvements in economic development. The study focused on Malawi which is still poor despite having adopted a series of policy interventions through the World Bank and International Monetary Fund-backed structural adjustment programs (SAPs). It further implemented the Poverty Reduction Strategy Papers (PRSP), Malawi Growth and Development Strategy papers (MGDS) 1-3) but poverty and underdevelopment continue to rise in Malawi. In this regard, the study aimed at finding what causes the persistent poverty and underdevelopment between the internalist and externalist forces. Further the study aimed at providing recommendations to addressing the governance gaps of compliance and collaboration, which entail policy implementation and effectiveness for the former and an effective nexus between the state and policy networks for the latter. With a postpositivist approach the study aimed at investigating what causes the continued poverty and underdevelopment in Malawi between the internal and external forces. Data was collected from officials in various government ministries and statutory entities as they were experts in the provision of public services and are either part of the governance machinery or institutions that aim at improving social economic welfare of the citizenry. Semi structured interviews were carried out and data was analysed in two parts, firstly using a Likert scale analysis, and secondly using thematic analysis for the qualitive responses from the interviewees. The study found that from a historical viewpoint colonialism played a role in establishing economic structures which are still present in post-colonial Malawi. In addition, the study found that internal factors such as poor leadership, lack of political will, corruption, and regime change in a democratically governed state contribute to persistent poverty and underdevelopment. The study established that Research Report Student: 1775131 iii improvement in these areas would bring about good governance which would i yield reduced poverty and improved social-economic development in the long term.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Governance; good governance; economic development; SDG-8: Decent work and economic growth